Food Estate - Jamson H Tampubolon; Delvian Delvian; Abdul Rauf (Jurnal Agribisnis Indonesia, 2024)
ABSTRACT Food functions as a pillar of national development and plays a role in maintaining a country’s economic, social and political stability of a country, all of which must be fulfilled by the state. Many countries are facing global food problems, leading to significant increases in commodity prices. The Indonesian government launched a National Food Storage Development Strategy to overcome the food crisis. The "Food estate" program aims to ensure that high-quality food is available, accessible and consumed by the public, and to increase domestic production. In North Sumatra, efforts to increase food security through the food estate program are considered the right solution. 215 hectares of land was converted into a horticultural area in Humbang HasundutanRegency. Horticultural crops developed in the HumbangHasundutan Regency food estate include potatoes, shallots, garlic and tomatoes. This research aim is to analyze the income from farming horticultural crops in the HumbangHasundutan food estate. This research data analysis uses farming income analysis. The analysis results show that the largest total income (Income) from farming is the potato plant, amounting to Rp. 371,184,000,-. The conclusion of this research is that of the 4 commodities, only 1 commodity made a profit, while the income of the other three commodities received a minus income value. Keywords: economy, food estate, farming, income, horticulture ABSTRAK ​Pangan berfungsi sebagai pilar pembangunan nasionaldan berperan dalam menjaga stabilitas ekonomi, sosial, dan politik suatu negara, yang semuanya harus dipenuhi oleh negara. Banyak negara menghadapi masalah pangan global, yang menyebabkan kenaikan harga komoditas yang signifikan. Pemerintah Indonesia meluncurkan StrategiPembangunan Lumbung Pangan Nasional untuk mengatasikrisis pangan. Program "Food estate" bertujuan untuk memastikan bahwa makanan berkualitas tinggi tersedia, dapatdiakses, dan dikonsumsi oleh masyarakat, serta untuk meningkatkan produksi dalam negeri. Di Sumatera Utara, upaya untuk meningkatkan ketahanan pangan melaluiprogram food estate dianggap sebagai solusi yang tepat. lahanseluas 215 hektar diubah menjadi area hortikultura di Kabupaten Humbang Hasundutan. Tanaman hortikultura yang dikembangkan di food estate Kabupaten HumbangHasundutan meliputi kentang, bawang merah, bawang putih, dan tomat. Tujuan penelitian ini adalah untuk menganalisispendapatan usahatani tanaman hortikultura di food estate Humbang Hasundutan. Analisis data penelitian ini menggunakan analisis pendapatan usaha tani. Hasil analasismenunjukkan bahwa menunjukkan bahwa total pendapatan(Income) usahatani yang paling besar adalah tanamankentang sebesar Rp. 371.184.000,-. Kesimpulan daripenelitian ini adalah bahwa dari 4 komoditi hanya 1 komoditiyang untung sedangkan pendapatan tiga komoditas lainnyamemperoleh nilai pendapatan yang minus. Kata Kunci: ekonomi, food estate, hortikultura, pendapatan, petani.